Potensi Pemanfaatan Sampah menjadi Energi di Kabupaten Tabalong (Provinsi Kalimantan Selatan) - Chaniago, Rian Yaitsar (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Energy is essential for well-being, health, and socio-economic development, and the consumption of fossil fuels has caused various harmful environmental impacts, such as global warming and environmental pollution. Waste-to-energy converts waste into energy, creating significant benefits for both waste management and energy security. The purpose of this study was to determine the potential utilization of waste to energy in Tabalong Regency. The method used is the approach of chemical characteristics of waste. The analysis results indicate that the chemical formula of Tabalong Regency's daily waste without sulfur content is C79H117O37N (without water) and C79H126O42N (with water). Meanwhile, the chemical formula with sulfur content is C937H1386O442N12S (without water) and C937H1502O501N12S (with water). The chemical formula of waste with sulfur was then analyzed to determine the Waste to Energy (WtE) potential of waste in Tabalong Regency. The analysis results reveal that the potential energy using wet weight is 9,309 Btu/day or 21,653 kJ/kg. While the potential energy if the waste uses dry weight is 9,800 Btu/day or 22,794 kJ/kg.